A review of carbon farming impacts on nitrogen cycling, retention, and loss. Issue 1 (27th September 2021) - Almaraz, Maya; Wong, Michelle Y.; Geoghegan, Emily K.; Houlton, Benjamin Z.
Abstract: Soil carbon (C) sequestration in agricultural working lands via soil amendments and management practices is considered a relatively well‐tested and affordable approach for removing CO2 from the atmosphere. Carbon farming provides useful benefits for soil health, biomass production, and crop resilience, but the effects of different soil C sequestration approaches on the nitrogen (N) cycle remain controversial. While some C farming practices have been shown to reduce N fertilizer use in some cases, C farming could also impose an unwanted "N penalty" through which soil C gains can only be maintained with additional N inputs, thereby increasing N losses to the environment. We systematically reviewed meta‐analysis studies on the impacts of C farming on N cycling in agroecosystems and estimated the cumulative effect of several C farming practices on N cycling. We found that, on average, combined C farming practices significantly reduced nitrous oxide emissions and nitrate leaching from soils, thus inferring both N cycling and climate change benefits. In addition to more widely studied C farming practices that generate organic C, we also discuss silicate rock additions, which offer a pathway to inorganic C sequestration that does not require additional N inputs, framing important questions for future research. Abstract : In this review, we synthesize data on how soil carbon (C) farming affects nitrogen (N) cycling. We systematically reviewing the literature; draw on the literature to discuss how C farming practices may interact with the N cycle and the potential benefits and consequences those interactions pose and identify research gaps that future C farming studies should seek to address; and aggregate C farming effect sizes on N cycling pathways and estimate the combined effect that multiple C farming practices could potentially have on N cycling if adopted at full capacity. We use this analysis to discuss whether the data suggest the existence of an N penalty or if C sequestration can be achieved while reducing N losses from agroecosystems.